Bilateral proptosis in a child: A rare presentation of acute lymphoblastic leukemia - Pon Ramya Sivaperumal; Sneha Magatha Latha; Sowmiya Narayani; Julius Scott (Journal of Ophthalmic & Vision Research, 2018)
Purpose: Acute lymphoblastic leukemia (ALL), a common hematological malignancy observed in children, typically presents with fever, pallor, easy bruising, hepatosplenomegaly and lymphadenopathy. However, when ALL manifests with unusual signs and the blood counts and peripheral smears are normal, it causes a diagnostic dilemma. Case Report: We report a 5-year-old boy who presented with bilateral proptosis as the initial manifestation of ALL. He presented with fever and bilateral knee pain attributed to a fall while playing. There was a history of progressive bilateral proptosis for a 3-month period not associated with any other complaints such as fever, eye pain, redness, or tearing. Thyroid function tests were normal. Blood counts acquired upon proptosis presentation were normal. When he presented to us three months later, blood counts revealed a pancytopenia but the peripheral smear showed no abnormal cells. Magnetic resonance imaging of the brain and orbits was normal. Bone marrow aspirate flow cytometry confirmed the diagnosis of B cell acute lymphoblastic lymphoma. Conclusion: Ophthalmologists should be aware of the unusual ophthalmologic manifestations of acute leukemia, as they may precede overt leukemia and cause diagnostic dilemmas. Knowledge about the rare and isolated extramedullary manifestations of ALL facilitates early diagnosis and thereby improves prognosis.